Psychological and social factors influencing patients' treatment selection for localised prostate cancer - Robles, Luke A.; Chou, Shihning; Cole, Owen J.; Hamid, Akhlil; Griffiths, Amanda; Vedhara, Kavita (Intech, 2013)
Chapter 3.